Neighborhood disadvantage and ischemic stroke: the Cardiovascular Health Study (CHS). - Brown, Arleen F; Liang, Li-Jung; Vassar, Stefanie D; Stein-Merkin, Sharon; Longstreth, W T; Ovbiagele, Bruce; Yan, Tingjian; Escarce, José J (Stroke, 2011)
BACKGROUND AND PURPOSE: Neighborhood characteristics may influence the risk of stroke and contribute to socioeconomic disparities in stroke incidence. The objectives of this study were to examine the relationship between neighborhood socioeconomic status and incident ischemic stroke and examine potential mediators of these associations. METHODS: We analyzed data from 3834 whites and 785 blacks enrolled in the Cardiovascular Health Study, a multicenter, population-based, longitudinal study of adults ages≥65 years from 4 US counties. The primary outcome was adjudicated incident ischemic stroke. Neighborhood socioeconomic status was measured using a composite of 6 census tract variables. Race-stratified multilevel Cox proportional hazard models were constructed adjusted for sociodemographic, behavioral, and biological risk factors. RESULTS: Among whites, in models adjusted for sociodemographic characteristics, stroke hazard was significantly higher among residents of neighborhoods in the lowest compared with the highest neighborhood socioeconomic status quartile (hazard ratio, 1.32; 95% CI, 1.01-1.72) with greater attenuation of the hazard ratio after adjustment for biological risk factors (hazard ratio, 1.16; 0.88-1.52) than for behavioral risk factors (hazard ratio, 1.30; 0.99-1.70). Among blacks, we found no significant associations between neighborhood socioeconomic status and ischemic stroke. CONCLUSIONS: Higher risk of incident ischemic stroke was observed in the most disadvantaged neighborhoods among whites, but not among blacks. The relationship between neighborhood socioeconomic status and stroke among whites appears to be mediated more strongly by biological than behavioral risk factors.
Keywords: Aged; Aged, 80 and over; Brain Ischemia; Female; Health Status Disparities; Humans; Incidence; Longitudinal Studies; Male; Poverty; Residence Characteristics; Risk; Risk Factors; Social Class; Social Environment; Socioeconomic Factors; Stroke; Urban Population

Exploring psychosocial pathways between neighbourhood characteristics and stroke in older adults: the cardiovascular health study. - Yan, Tingjian; Escarce, José J; Liang, Li-Jung; Longstreth, W T; Merkin, Sharon Stein; Ovbiagele, Bruce; Vassar, Stefanie D; Seeman, Teresa; Sarkisian, Catherine; Brown, Arleen F (Age Ageing, 2013)
OBJECTIVES: to investigate whether psychosocial pathways mediate the association between neighbourhood socioeconomic disadvantage and stroke. METHODS: prospective cohort study with a follow-up of 11.5 years. SETTING: the Cardiovascular Health Study, a longitudinal population-based cohort study of older adults ≥65 years. MEASUREMENTS: the primary outcome was adjudicated incident ischaemic stroke. Neighbourhood socioeconomic status (NSES) was measured using a composite of six census-tract variables. Psychosocial factors were assessed with standard measures for depression, social support and social networks. RESULTS: of the 3,834 white participants with no prior stroke, 548 had an incident ischaemic stroke over the 11.5-year follow-up. Among whites, the incident stroke hazard ratio (HR) associated with living in the lowest relative to highest NSES quartile was 1.32 (95% CI = 1.01-1.73), in models adjusted for individual SES. Additional adjustment for psychosocial factors had a minimal effect on hazard of incident stroke (HR = 1.31, CI = 1.00-1.71). Associations between NSES and stroke incidence were not found among African-Americans (n = 785) in either partially or fully adjusted models. CONCLUSIONS: psychosocial factors played a minimal role in mediating the effect of NSES on stroke incidence among white older adults.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Aging; Brain Ischemia; Depression; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Linear Models; Logistic Models; Male; Middle Aged; Proportional Hazards Models; Prospective Studies; Residence Characteristics; Risk Assessment; Risk Factors; Social Support; Socioeconomic Factors; Stroke; Time Factors; United States; Vulnerable Populations

Neighborhood socioeconomic disadvantage and mortality after stroke. - Brown, Arleen F; Liang, Li-Jung; Vassar, Stefanie D; Merkin, Sharon Stein; Longstreth, W T; Ovbiagele, Bruce; Yan, Tingjian; Escarce, José J (Neurology, 2013)
OBJECTIVE: Residence in a socioeconomically disadvantaged community is associated with mortality, but the mechanisms are not well understood. We examined whether socioeconomic features of the residential neighborhood contribute to poststroke mortality and whether neighborhood influences are mediated by traditional behavioral and biologic risk factors. METHODS: We used data from the Cardiovascular Health Study, a multicenter, population-based, longitudinal study of adults ≥65 years. Residential neighborhood disadvantage was measured using neighborhood socioeconomic status (NSES), a composite of 6 census tract variables representing income, education, employment, and wealth. Multilevel Cox proportional hazard models were constructed to determine the association of NSES to mortality after an incident stroke, adjusted for sociodemographic characteristics, stroke type, and behavioral and biologic risk factors. RESULTS: Among the 3,834 participants with no prior stroke at baseline, 806 had a stroke over a mean 11.5 years of follow-up, with 168 (20%) deaths 30 days after stroke and 276 (34%) deaths at 1 year. In models adjusted for demographic characteristics, stroke type, and behavioral and biologic risk factors, mortality hazard 1 year after stroke was significantly higher among residents of neighborhoods with the lowest NSES than those in the highest NSES neighborhoods (hazard ratio 1.77, 95% confidence interval 1.17-2.68). CONCLUSION: Living in a socioeconomically disadvantaged neighborhood is associated with higher mortality hazard at 1 year following an incident stroke. Further work is needed to understand the structural and social characteristics of neighborhoods that may contribute to mortality in the year after a stroke and the pathways through which these characteristics operate.
Keywords: Aged; Female; Humans; Incidence; Kaplan-Meier Estimate; Male; Proportional Hazards Models; Residence Characteristics; Risk Factors; Socioeconomic Factors; Stroke; Vulnerable Populations

Stroke genetics informs drug discovery and risk prediction across ancestries. - Mishra, Aniket; Malik, Rainer; Hachiya, Tsuyoshi; Jürgenson, Tuuli; Namba, Shinichi; Posner, Daniel C; Kamanu, Frederick K; Koido, Masaru; Le Grand, Quentin; Shi, Mingyang; He, Yunye; Georgakis, Marios K; et al. (Nature, 2022)
Previous genome-wide association studies (GWASs) of stroke - the second leading cause of death worldwide - were conducted predominantly in populations of European ancestry. Here, in cross-ancestry GWAS meta-analyses of 110,182 patients who have had a stroke (five ancestries, 33% non-European) and 1,503,898 control individuals, we identify association signals for stroke and its subtypes at 89 (61 new) independent loci: 60 in primary inverse-variance-weighted analyses and 29 in secondary meta-regression and multitrait analyses. On the basis of internal cross-ancestry validation and an independent follow-up in 89,084 additional cases of stroke (30% non-European) and 1,013,843 control individuals, 87% of the primary stroke risk loci and 60% of the secondary stroke risk loci were replicated (P < 0.05). Effect sizes were highly correlated across ancestries. Cross-ancestry fine-mapping, in silico mutagenesis analysis, and transcriptome-wide and proteome-wide association analyses revealed putative causal genes (such as SH3PXD2A and FURIN) and variants (such as at GRK5 and NOS3). Using a three-pronged approach, we provide genetic evidence for putative drug effects, highlighting F11, KLKB1, PROC, GP1BA, LAMC2 and VCAM1 as possible targets, with drugs already under investigation for stroke for F11 and PROC. A polygenic score integrating cross-ancestry and ancestry-specific stroke GWASs with vascular-risk factor GWASs (integrative polygenic scores) strongly predicted ischaemic stroke in populations of European, East Asian and African ancestry. Stroke genetic risk scores were predictive of ischaemic stroke independent of clinical risk factors in 52,600 clinical-trial participants with cardiometabolic disease. Our results provide insights to inform biology, reveal potential drug targets and derive genetic risk prediction tools across ancestries.